Indonesian Policy in Ratifying The 2015 Paris Agreement - Siraj, Haekal (UI Scholars Hub, 2019)
The 2015 Paris Agreement requires all participating countries to reduce emisson level. Indonesia as Non-Annex I accepted the norms of the 2015 Paris Agreement by ratifying this agreement. Meanwhile, Indonesia's emissions level continues to increase due to the rate of deforestation and forest degradation in Indonesia which ranks highest in the world. This study aims to analyze Indonesian policy in ratifying the agreement by using the Constructivism Perspective in explaining the International Regime and the Concept of Norm Influence by Finnemore and Sikkink. The study uses qualitative methods with explanatory designs. Data collection techniques are sourced from secondary sources as well as data analysis techniques carried out by reduction, presentation, and drawing conclusions as well as verification. This study found that the United States as a hegemonic state acting as the norm entrepreneurs by granting climate change financial assistance of 500 million through the GCF for Indonesia as a developing country was a condition affecting Indonesia in ratifying the agreement. Keywords: Indonesia, ratify, 2015 Paris Agreement, norm, climate change.